2015
DOI: 10.1016/j.clinph.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robotic-locomotor training on stretch reflex function and muscular properties in individuals with spinal cord injury

Abstract: Objective We sought to determine the therapeutic effect of robotic-assisted step training (RAST) on neuromuscular abnormalities associated with spasticity by characterization of their recovery patterns in people with spinal cord injury (SCI). Methods Twenty-three motor-incomplete SCI subjects received one-hour RAST sessions three times per week for four weeks, while an SCI control group received no training. Neuromuscular properties were assessed using ankle perturbations prior to and during the training, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…From the 18 studies, 7 trials were done in the United States [36][37][38][39][40][41][42], 2 in Spain [43,44], 2 in Switzerland [45,46], 2 in Canada [47,48], 2 in Italy [49,50], 2 in Japan [51,52], and one in Germany [53].…”
Section: Study Locationmentioning
confidence: 99%
“…From the 18 studies, 7 trials were done in the United States [36][37][38][39][40][41][42], 2 in Spain [43,44], 2 in Switzerland [45,46], 2 in Canada [47,48], 2 in Italy [49,50], 2 in Japan [51,52], and one in Germany [53].…”
Section: Study Locationmentioning
confidence: 99%
“…The mean distance walked was 2,271 m (SD 465 m), and the mean body-weight support was 40% (SD 21%), with a guidance force of 82% (SD 8%) per training session. chronic SCI without baseline gait function are able to regain functional walking (5,10,11). However, even among non-walkers, there appear to be some benefits of gait training, such as improved VO 2 and neuromuscular control (9,10).…”
Section: Resultsmentioning
confidence: 99%
“…It was decided to include subjects with poor baseline walking function since data on their training effects are more limited. Mirbagheri et al (10) found that subjects with more baseline neuromuscular disturbances were more likely to have reduced spasticity after RALT. Based on studies so far, including meta-analyses (8), the effects of RALT on walking function remain inconclusive, and it is still unclear whether subjects with Table II.…”
Section: Baseline Function May Be Importantmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gait training interventions, there is a predominance of studies with incomplete SCI patients, given the greater potential for functional gait recovery for these individuals. In addition, 2 studies 33,36 indicate that ambulating individuals-who present the highest initial gait deficits, as indicated by a lower speed and resistance of the initial gait-present greater potential for Physical Exercise in SCI: Systematic Review improvement from the interventions. Interventions that focused on balance training included individuals with tetraplegia and paraplegia with incomplete SCI (classified ASIA Impairment Scale C-D).…”
Section: Characteristics Of Subjectsmentioning
confidence: 99%